Power laws in art: From Renaissance to contemporary art - Federico Etro; Elena Stepanova (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2018)
We provide evidence of a cubic law of art prices that hints to a general pattern for the distribution of artistic talent. The persistence across heterogeneous markets from historical ones to contemporary art auctions of a power law in the distribution of the average price per artist suggests the possibility of a universal law for talent distribution. We explore scale-free networks of teacher-students to investigate the diffusion of talent over time.
Keywords: C23; Z11; 330; Power laws; Art prices; Talent distribution; Scale-free networks